2017
DOI: 10.3390/ijerph14090974
|View full text |Cite
|
Sign up to set email alerts
|

Association between Blood Pressure and Birth Weight among Rural South African Children: Ellisras Longitudinal Study

Abstract: The aim of this cross-sectional study was to investigate the association between birth weight, underweight, and blood pressure (BP) among Ellisras rural children aged between 5 and 15 years. Data were collected from 528 respondents who participated in the Ellisras Longitudinal Study (ELS) and had their birth weight recorded on their health clinic card. Standard procedure was used to measure the anthropometric measurements and BP. Linear regression was used to assess BP, underweight variables, and birth weight.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
20
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(22 citation statements)
references
References 38 publications
0
20
0
2
Order By: Relevance
“…Preliminary Ellisras Longitudinal Study (ELS) results reported a high prevalence of under-nutrition amongst older children (7-10 years) compared to younger children [10,20]. Furthermore, Monyeki et al [21] reported the association between hypertension and under-nutrition amongst younger children whose birth weights were recorded while Mphekgwane et al [22] reported no significant association between hypertension and under-nutrition in younger ELS children (age 5-15 years). The aim of this study, therefore, was to determine the association between under-nutrition and hypertension among older Ellisras children and adolescents aged 9-17 years.…”
Section: Introductionmentioning
confidence: 99%
“…Preliminary Ellisras Longitudinal Study (ELS) results reported a high prevalence of under-nutrition amongst older children (7-10 years) compared to younger children [10,20]. Furthermore, Monyeki et al [21] reported the association between hypertension and under-nutrition amongst younger children whose birth weights were recorded while Mphekgwane et al [22] reported no significant association between hypertension and under-nutrition in younger ELS children (age 5-15 years). The aim of this study, therefore, was to determine the association between under-nutrition and hypertension among older Ellisras children and adolescents aged 9-17 years.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, a sizeable Mendelian randomization analysis failed to detect an inverse relationship between birth weight and blood pressure [15]. Another similar study on birth weight and blood pressure in rural subjects also highlighted this issue [17].…”
Section: Introductionmentioning
confidence: 99%
“…However, the current research on the relationship between birth weight and blood pressure is partly controversial and even completely contradictory [15][16][17]. Lai C et al [16] found a U-shaped relationship between birth weight and blood pressure, especially SBP.…”
Section: Introductionmentioning
confidence: 99%
“…Birth weight (BW) is considered a significant indicator for assessing fetal intrauterine growth, the nutritional condition and the health status of newborns, as well as predicting growth, developmental status, and health problems in adulthood [1][2][3]. In newborns with a normal weight, those with a low birth weight and macrosomia are related to higher morbidity and mortality [4][5][6], and low birth weight can result in poor mental development, risk of infection, and risk of developing cardiovascular disease later in life [7][8][9].…”
Section: Introductionmentioning
confidence: 99%